2010
DOI: 10.12693/aphyspola.117.808
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modifications of a Ti6Al4V Alloy by a Laser Shock Processing

Abstract: The influence of the Laser Shock Processing (LSP) on the morphology, microstructure and surface layer properties of a Ti6Al4V alloy has been studied. Residual stresses were assessed as well. For the Laser Shock Processing a 1 KW, high-power Q-switched Nd:YAG laser was used. During the process the surface of the investigated material was covered by series of single, partially overlapping impulses. The laser power density was a 1 GW/cm 2 and a pulse duration of 18 ns. The microstructure and the phases presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The nanohardness values measured on the polished cross-sections showed that the hardness of the layer contained martensite and a high density of dislocations (approximately up to 0.5 mm) which was much higher (varied between 360 -480 nHV) than that of the matrix (290 nHV). Also the Young's modulus values of the investigated internal deformed surface layer (140 GPa) was slightly higher than that of the matrix (127 GPa)-as reference see [124,126].…”
Section: Laser Shock Processingmentioning
confidence: 81%
See 3 more Smart Citations
“…The nanohardness values measured on the polished cross-sections showed that the hardness of the layer contained martensite and a high density of dislocations (approximately up to 0.5 mm) which was much higher (varied between 360 -480 nHV) than that of the matrix (290 nHV). Also the Young's modulus values of the investigated internal deformed surface layer (140 GPa) was slightly higher than that of the matrix (127 GPa)-as reference see [124,126].…”
Section: Laser Shock Processingmentioning
confidence: 81%
“…Water decreases the expansion of plasma in the surrounding atmosphere and produces up to ten time's higher pressure on the material surface. The pressure propagating into the treated material as a shock wave can induce microstructural changes, cause a high increase of dislocation density, influence the surface roughness of the material as well as produce high residual surface compressive stresses [122][123][124][125]. If the surface is insulated from the increasing temperature by a protective absorbing layer, the laser treatment becomes purely mechanical.…”
Section: Laser Shock Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the technique was initially developed for the improvement of the fatigue cracking resistance of materials used in the aeronautic applications (specifically Aluminum alloys), Titanium alloys and different types of stainless steels are being extensively investigated in the frame of different areas of application, especially the aerospatial sector itself but also in the nuclear, automotive and biomedical sectors on the basis of the commercial availability of new powerful laser sources able to provide intensities exceeding the GW/cm 2 level [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%